Effectiveness of Foot Reflexology on Depression among Old Age People (International Journal of Nursing Education, 2020)
Depression is the most common mental disorder among old age in India and one of the most disablingcondition worldwide. It is difficult to differentiate clinical symptoms of depression in old age from symptomsof normal ageing. Depression is found among 15% to 50% of residents in long term care depending on oldage home. It is possible to improve mental capacities and coping skills that are affected by depression withdaily activities that delay the onset of behavioural disturbances and reduce caring time. Foot reflexologywould be the tool that may help to preserve mental capacity of old age people. The study was conducted toevaluate the effectiveness of foot reflexology on level of depression among old age people. Pre experimentalone group pre-test post-test design was adopted to evaluate the effectiveness of foot reflexology on levelof depression among old age people. 50 participants were selected using purposive sampling technique.Yesavage’s Geriatric Depression scale was used to assess the level of depression among old age people.Pre-test was done among old age people with depression and foot reflexology was given to the selectedparticipants with mild and severe depression for 20 minutes, once in every three days for 10 sessions. Thepost-test was done after the intervention with the same scale. Findings reveals that pre-test score of depressionamong old age people, none of them were normal, 38(76%) of them had mild depression, 12(24%) of themhad severe depression. While analysing the post-tests core of depression among old age people, 26(52%)of them were normal, 18(36%) of them had mild depression, 6(12%) of them had severe depression. Themean pre-test value was 17.94, the mean post-test value was 10.86,the standard deviation was 4.948 andthe calculated ‘t’ value was 26.2*. The calculated ‘t’ value was greater than the table value, so there was asignificant difference between pre-test and post-test score. Hence the research hypothesis (H1) is accepted.The score represents that foot reflexology was effective in reducing the depression among old age people.
Keywords: Effectiveness, foot reflexology, depression, old age people.